Moving beyond the challenges and seizing the opportunities: A study of South African universities’ efforts to protect their research and innovation offerings during the COVID-19 pandemic - Malherbe, C.; Schutte, C. (South African Journal of Higher Education, 2021)
Like all organisations globally, South African universities were caught off-guard by the impact of the COVID-19 pandemic. To manage its financial and contractual/legal risks when faced with a threat such as a pandemic, an organisation needs integrated insight through the use of available information to assess possible disruptions and to be able to respond appropriately. This study analyses the status of South African universities in respect of their research and innovation offerings, and in particular the nature of their research contracts and their ability to respond to a threat such as COVID-19. Interviews were conducted with senior managers in seven South African universities. Some of the themes that emerged from these interviews were analysed using extracts from the financial management maturity model (FMMM) (Comptroller and Auditor General 2018). It was reassuring to find that the contractual risks can mostly be mitigated. However, the lack of strategic information and lower financial management maturity levels made it difficult for most universities to assess the financial impact of this pandemic and to respond appropriately.